Pentingkah Perilaku Wanita? Studi Kebijakan Dividen - Vivian Vivian; Candy Candy; Robin Robin (Politeknik Ganesha Medan, 2022)
Board diversity in the corporate governance function have multiple perspectives and active oversight in evaluating management decisions and through their influence on dividend policy. Therefore, this study examines the effect of female boards on the dividend payout ratio and dividend yield in a sample of companies in the IDX HIDIV20 and IDX BUMN20 for the period 2017-2020. The results showed that the percentage of female directors, female independent directors, female executive directors, and the numerical number of female directors had a significant positive effect on the dividend payout ratio. Women's associations and dividend policy have a stronger relationship when women on the board of directors have a high percentage. A certain number of women's councils were judged to be better and more effective in decision-making. While the female CEO as a leader because of risk-averse behavior, low self-confidence, weak decisions, and lack of control on the board, affect the value of the company including influencing dividend payments inversely. The results of this study provide strong evidence plus difference test and robustness test confirming that female boards facilitate corporate governance and promote dividend payouts further.